Collaborative Learning Stimulation to Address Learning Loss in Early Childhood - Sufa, Feri Faila; Yuli Setiawan, M Hery (Al-Khidmat : Jurnal Ilmiah Pengabdian Kepada masyarakat, 2024)
Abstrak Berkolaborasi dapat dikenalkan pada anak sejak dini. Pandemi Covid-19 memberikan dampak pada anak saat penerapan kebijakan Belajar dari Rumah. Hal ini karena tidak semua orang tua dapat memberikan stimulasi yang efektif. Hal ini karena perbedaan kemampuan orang tua dan kesulitan membagi waktu dengan kesibukan lainnya. Akibatnya anak usia dini banyak yang mengalami learning loss. Kegiatan Pengabdian ini ditujukan untuk melatih pendidik dalam memberikan stimulasi akibat leraning loss di masa Pandemi. Melalui sosialisasi IPTEK dalam stimulasi anak diharapkan aspek perkembangan anak dapat diakselerasikan dan berkembang optimal. Hasil dari kegiatan ini menunjukkan bahwa kemampuan pendidik meningkat dalam mengoptimalkan berbagai aspek perkembangan anak, baik dalam aspek sosial, kognitif, bahasa, dan nilai moral. Abstract Collaborating can be introduced to children from an early age. The Covid-19 pandemic has an impact on children when implementing the Study from Home policy. This is because not all parents can provide effective stimulation. This is due to differences in the ability of parents and difficulty in dividing time with other activities. As a result, many young children experience learning loss. This service activity is intended to train teachers in providing stimulation due to learning loss during the Pandemic. Through the socialization of science and technology in stimulating children, it is hoped that aspects of child development can be accelerated and develop optimally. The results of this activity indicate that the ability of teachers to increase in optimizing various aspects of children’s development, both in terms of social, cognitive, language, and moral values.. Keywords: Collaborative learning, Learning Loss, Early childhood.